Architectural studies and research at the universidad nacional de colombia (1937-1965). a look at the proceedings of the art´s faculty council. (2005)
What characterizes the academic research carned on inthe university? Which are the methods, instruments,and mechanisms applied on architectural research? Whatare the objectives, purposes, and targets, products andresults of architectural academic research? This articledoes not seek to answer these polemic questions. It isonly the first approach to the information recovery processof the university records. These dates coincide with theinaguration of the carrermof architecture in NationalUniversity of Colombia and with the profound transformationsintroduced by “Patiño’s reform”.